Preparation of hypercrosslinked PolyHIPEs by using a bio-derived monomer - Kekevi, Burcu; Mert, E. Hilal (European polymer journal, 2021)
[Display omitted] •A terpene derivative was used as a sustainable monomer for the synthesis of macroporous polymers.•Water-in-oil (w/o) type high internal phase emulsions (HIPEs) of β-myrcene were prepared.•Crosslinking of HIPEs was performed by using mixtures of DVB, VBC and BDDA comonomers.•The effect of monomer composition on the crosslinking of β-myrcene based HIPEs was demonstrated.•The specific surface area of polyHIPEs was significantly improved by hyper-crosslinking based on Friedel-Crafts alkylation. The interest on adapting bio-derived species to polymer synthesis has been increased in the last decade. Terpenes that can be obtained by extracting from the essential oils of tree sap and citrus fruit have an important place on this subject. In this respect, β-myrcene, which is a promising linear conjugated diene, is attracting the interest of researchers. However, the free radical copolymerization of β-myrcene is difficult mainly because of concurrent Diels-Alder reactions with electron-deficient vinyl monomers via their s-cis forms. Here, we developed polyHIPEs from the high internal phase emulsions (HIPEs) of β-myrcene. For this purpose, HIPEs were prepared by using either 50 or 40 vol% of β-myrcene in the continuous phase. Meanwhile, the influence of 4-vinylbenzyl chloride (VBC), divinylbenzene (DVB), and 1,3-butanedioldiacrylate (BDDA) on the copolymerization crosslinking of β-myrcene within precursor HIPEs was explored. For this purpose, HIPEs were prepared by altering the amount of comonomers between 0 and 60 vol% of the total monomer composition. The resulting HIPEs showed excellent stability. However, crosslinking could not be achieved in all cases, due to the altered monomer composition. On the other hand, crosslinked polyHIPEs were hypercrosslinked with Friedel-Crafts alkylation method. Characterization of the resulting materials showed the Brunauer-Emmett-Teller specific surface area (δBET) of the polyHIPEs was increased from 2.25 m2 g−1 to 60.18 m2 g−1 by hypercrosslinking.